2018
DOI: 10.1071/ah16171
|View full text |Cite
|
Sign up to set email alerts
|

Do acute hospitalised patients in Australia have a different body mass index to the general Australian population: a point prevalence study?

Abstract: Objective The aim of the present study was to provide a current snapshot of the body mass index (BMI) of the entire patient cohort of an Australian tertiary hospital on one day and compare these data with current published Australian and state (Western Australia) population norms. Methods A single-centre prospective point prevalence study was performed whereby BMI was calculated following actual measurement of patient weight (nurse) and height (physiotherapist) on one day during 2015. Variables were summarised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…This poor capture of patient anthropometry is disappointing but not unusual. However, the BMI distribution in our study matches another recent Australian study [48], which captured data of all hospitalised patients. The retrospective design of this study is another limitation because of possibility of unknown confounders which could have influenced our results.…”
Section: Limitationssupporting
confidence: 67%
“…This poor capture of patient anthropometry is disappointing but not unusual. However, the BMI distribution in our study matches another recent Australian study [48], which captured data of all hospitalised patients. The retrospective design of this study is another limitation because of possibility of unknown confounders which could have influenced our results.…”
Section: Limitationssupporting
confidence: 67%
“…However, specific evidence is limited regarding the prevalence of obesity amongst inpatients of acute hospitals in Australia and the subsequent impact of obesity on the costs of those admissions. To our knowledge, the only study conducted within an Australian tertiary hospital of the point prevalence of obesity amongst inpatients reported a rate similar to local population norms of 25%, but with an over-representation of people classified as obesity class II and higher (BMI ≥ 35 kg/m 2 ) [7]. Internationally, studies consistently report that a considerable proportion of healthcare dollars is spent on the treatment and management of obesity-related conditions; however, the direct cost of obesity on hospital admissions remains unclear [8][9][10].…”
Section: Introductionmentioning
confidence: 54%
“…In order to understand the potential influence of regional factors on prevalence rates of obese patients within acute hospitals, the findings from the present study make for an interesting comparison to those of a study conducted in a tertiary hospital in Perth, Western Australia. Dennis and colleagues [7] performed a point prevalence study of BMI in 2015 at a single institution of a similar size to Site B in the present study. The prevalence of overweight and obese inpatients was 32.4% and 22.3%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Two investigators (DD and JH) undertook a single centre retrospective case note review of an opportunistic sample of patients previously identified as having extremely abnormal body mass index during a prospective point prevalence study during 2015 [7]. At the beginning of the review, both investigators extracted data from 2 sets of notes and compared information.…”
Section: Design Setting and Processmentioning
confidence: 99%
“…According to both the World Health Organisation [1] and Australian Department of Health BMI guidelines [2], a person may be classified as underweight (< 18.5 Although there is much data pertaining to the BMI of the general Australian population [3,4], with regular Australian Bureau of Statistics reports around Australian population health statistics, little data exists describing the hospitalised cohort [5,6]. Our group recently established that underweight and extremely obese patients were over-represented during a point prevalence study of patients admitted to an Australian tertiary hospital [7]. It has been identified in the literature that these cohorts are expensive to manage, using more resources during hospital admission compared to patients in the…”
Section: Introductionmentioning
confidence: 99%